Workplace injuries, safety climate and behaviors: application of an artificial neural network. Issue 4 (1st October 2020) - Abubakar, A. Mohammed; Karadal, Himmet; Bayighomog, Steven W.; Merdan, Ethem
Abstract : This article proposes and tests a model for the interaction effect of the organizational safety climate and behaviors on workplace injuries. Using artificial neural network and survey data from 306 metal casting industry employees in central Anatolia, we found that an organizational safety climate mitigates workplace injuries, and safety behaviors enforce the strength of the negative impact of the safety climate on workplace injuries. The results suggest a complex relationship between the organizational safety climate, safety behavior and workplace injuries. Theoretical and practical implications are discussed in light of decreasing workplace injuries in the Anatolian metal casting industry.